2001
DOI: 10.1016/s0165-0173(01)00092-3
|View full text |Cite
|
Sign up to set email alerts
|

Plasticity of the human motor cortex and recovery from stroke

Abstract: By a variety of mechanisms, the human brain is constantly undergoing plastic changes. Plasticity can be studied with phenomena such as peripheral deafferentation and motor learning. Spontaneous recovery from stroke in the chronic stage likely comes about because of plasticity, and the best recovery seems to result from reorganization in the damaged hemisphere. Knowledge about the physiology of brain plasticity has led to the development of new techniques for rehabilitation. Published by Elsevier Science B. V. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
179
0
9

Year Published

2002
2002
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 319 publications
(195 citation statements)
references
References 64 publications
7
179
0
9
Order By: Relevance
“…Stinear and Byblow argued that progress toward motor recovery may be advanced when patients received rehabilitation protocols within Stroke, NIBS, and Rehabilitation 15 six months post a stroke, during the spontaneous recovery period [69]. Specifically, the effects of neuromodulation interventions on neural plasticity and reorganization of brain activation between hemispheres may increase during the spontaneous recovery period in comparison to the chronic stage [69,70]. Thus, further studies investigating the different effects of NIBS techniques based on post stroke recovery stages will be necessary.…”
Section: Discussionmentioning
confidence: 99%
“…Stinear and Byblow argued that progress toward motor recovery may be advanced when patients received rehabilitation protocols within Stroke, NIBS, and Rehabilitation 15 six months post a stroke, during the spontaneous recovery period [69]. Specifically, the effects of neuromodulation interventions on neural plasticity and reorganization of brain activation between hemispheres may increase during the spontaneous recovery period in comparison to the chronic stage [69,70]. Thus, further studies investigating the different effects of NIBS techniques based on post stroke recovery stages will be necessary.…”
Section: Discussionmentioning
confidence: 99%
“…Motor networks in surviving peri-infarct regions, as well as the undamaged contralateral homotopic cortex and subcortical structures, demonstrate significant reorganization after stroke [55][56][57]. Plasticity in these areas is believed to support functional recovery [58]. As detailed above, a study from Porter et al [36] demonstrated that VNS paired with forelimb training drives robust, specific plasticity within motor cortex.…”
Section: Preclinical and Clinical Studies For Ischemic Strokementioning
confidence: 99%
“…This subacute recovery in motor function can be explained in part by neural reorganization caused by rehabilitation training [8][9][10][11][12]. It is suggested that key factors to upperlimb stroke rehabilitation training are attention, repetition, intensity of practice, reward, progression of complexity, and skill acquisition and that this training should be task-oriented [12][13].…”
Section: Introductionmentioning
confidence: 99%